2018
DOI: 10.1111/pan.13405
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prophylactic dexmedetomidine in preventing postoperative junctional ectopic tachycardia in pediatric cardiac surgery patients: A systematic review and meta‐analysis

Abstract: Prophylactic dexmedetomidine is effective in reducing the incidence of postoperative junctional ectopic tachycardia without significant increases in adverse events in pediatric patients undergoing surgery for congenital heart diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Dexmedetomidine was administered in all patients undergoing surgery on induction of anesthesia at the dose of 0.5 μg/kg/min and continued in the postoperative period. 32,33 Junctional ectopic tachycardia was diagnosed in the intensive care unit by standard 12-lead ECG on the basis of criteria described earlier. 16 Atrial lead ECG was done when the diagnosis was in doubt.…”
Section: Methodsmentioning
confidence: 99%
“…Dexmedetomidine was administered in all patients undergoing surgery on induction of anesthesia at the dose of 0.5 μg/kg/min and continued in the postoperative period. 32,33 Junctional ectopic tachycardia was diagnosed in the intensive care unit by standard 12-lead ECG on the basis of criteria described earlier. 16 Atrial lead ECG was done when the diagnosis was in doubt.…”
Section: Methodsmentioning
confidence: 99%
“…836 Intraoperative and postoperative administration of dexmedetomidine might reduce the occurrence of postoperative JET. 933, 934 On the other hand, congenital or non-surgical JET might be controlled by single use or combination of amiodarone, β-blocker, and Class IC drug. 927 ▋ 1.3.4 Permanent Junctional Reciprocating Tachycardia Permanent junctional reciprocating tachycardia (PJRT) is a long RP' narrow QRS tachycardia due to a rare form of accessory pathway with decremental conduction properties and usually located in the posteroseptal region of tricuspid annulus.…”
Section: B Pharmacotherapymentioning
confidence: 99%
“…In the PICU setting, DEX has been shown to be effective as a prophylactic treatment for junctional ectopic tachycardia (JET) in post-cardiac surgery. A metanalysis of seven randomized controlled trials representing 1616 patients reported a significant reduction in JET, ICU stay, and duration of mechanical ventilation in those who received DEX [128]. Caution should be considered in the long-term use of DEX infusions, as there is a case report which describes supraventricular tachycardia during DEX weaning of a 4-year-old without pre-existing cardiac disease [129].…”
Section: Pediatric Intensive Care Unitmentioning
confidence: 99%